Measurements of the solubilities of some silver halides in water by electrical methods - Malan, George McPherson (Rhodes University, Faculty of Science, Department of Chemistry, 1955)
[Introduction, p. 3] The solubilities of the silver halides cannot be determined by the conventional methods of analytical chemistry because they are too sparingly soluble (of the order 1 x 10â »â µ to 1 x 10â »â ¶ g . equiv./1. at 25Â°C.) However, electrical, and to a lesser extent optical methods, are admirably suited because of their greater sensitivity. The conductometric and potentiometric methods are the two most important electrical techniques for the measurement of the solubilities of sparingly soluble salts, and are the ones employed in this research. There are large discrepancies between the published values for the solubility of silver chloride. Results obtained by the conductometric and potentiometric methods disagree. In addition, figures quoted by independent authors using the same method differ by as much as 15%.
Keywords: Silver halides -- Solubility; Silver halides -- Analysis; Conductometric analysis; Potentiometry; Silver halides